If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3n + 2) = 7(4n + 9) + 4 Reorder the terms: 2(2 + 3n) = 7(4n + 9) + 4 (2 * 2 + 3n * 2) = 7(4n + 9) + 4 (4 + 6n) = 7(4n + 9) + 4 Reorder the terms: 4 + 6n = 7(9 + 4n) + 4 4 + 6n = (9 * 7 + 4n * 7) + 4 4 + 6n = (63 + 28n) + 4 Reorder the terms: 4 + 6n = 63 + 4 + 28n Combine like terms: 63 + 4 = 67 4 + 6n = 67 + 28n Solving 4 + 6n = 67 + 28n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-28n' to each side of the equation. 4 + 6n + -28n = 67 + 28n + -28n Combine like terms: 6n + -28n = -22n 4 + -22n = 67 + 28n + -28n Combine like terms: 28n + -28n = 0 4 + -22n = 67 + 0 4 + -22n = 67 Add '-4' to each side of the equation. 4 + -4 + -22n = 67 + -4 Combine like terms: 4 + -4 = 0 0 + -22n = 67 + -4 -22n = 67 + -4 Combine like terms: 67 + -4 = 63 -22n = 63 Divide each side by '-22'. n = -2.863636364 Simplifying n = -2.863636364
| 11x-9=4x+68 | | -12c+16c=-12 | | 80=5(5n-4) | | v+7/2=3 | | 3y+5y=13 | | 4x+7=3+2x+22 | | -3m^2+16=-284 | | 10k-6=-156 | | -2(x+2)-3(x+6)=-22 | | 4x^2+81=17 | | 3x=15x^2 | | (5x^2)-(6x)-(2)=0 | | x(-4)=8 | | -7(-3x+3)=-105 | | (-5)*x=1/2 | | -2(n-3)=-4 | | 9(x+7)=81 | | x*3/8=-2 | | 3h-h=12 | | 5(x+9)+5=50 | | 3x^2-4x=11 | | 4z+2(z-1)=1-2(z-1) | | 3*(-1/8)=2-x | | 2x-8x-10=-6x+7-10 | | 3(x-2)-5=6x-3(5+x) | | 2y^2-8y+y-12y^2-8y+7= | | -15=2t+13 | | 3*(-1/8)=x | | 6x+64-3x-10= | | 4a^2-b^2=0 | | 3*(-3/8)=-1,6 | | 2x+18=4x-30 |